2022
DOI: 10.3390/toxins14030205
|View full text |Cite
|
Sign up to set email alerts
|

The Isolated Mouse Jejunal Afferent Nerve Assay as a Tool to Assess the Effect of Botulinum Neurotoxins in Visceral Nociception

Abstract: For the past two decades, botulinum neurotoxin A (BoNT/A) has been described as a strong candidate in the treatment of pain. With the production of modified toxins and the potential new applications at the visceral level, there is a real need for tools allowing the assessment of these compounds. In this study, we evaluated the jejunal mesenteric afferent nerve assay to investigate BoNT/A effects on visceral nociception. This ex vivo model allowed the continuous recording of neuronal activity in response to var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Immunohistochemical staining was performed using an avidin-biotin-peroxidase protocol as previously described [18,58]. Sections to be incubated with the anti-SNAP-25 antibody did not receive antigen retrieval, whereas those to be stained with the anticleaved SNAP-25 (anti-cSNAP-25) antibody were immersed in EDTA buffer (pH 9, Sigma-Aldrich, Gillingham, UK, E9884) at 98 • C. All sections were first blocked with 3% hydrogen peroxide (Sigma-Aldrich, Gillingham, UK, 1.07209), followed by 10% serum (Sigma-Aldrich, H1270) in Dako buffer.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunohistochemical staining was performed using an avidin-biotin-peroxidase protocol as previously described [18,58]. Sections to be incubated with the anti-SNAP-25 antibody did not receive antigen retrieval, whereas those to be stained with the anticleaved SNAP-25 (anti-cSNAP-25) antibody were immersed in EDTA buffer (pH 9, Sigma-Aldrich, Gillingham, UK, E9884) at 98 • C. All sections were first blocked with 3% hydrogen peroxide (Sigma-Aldrich, Gillingham, UK, 1.07209), followed by 10% serum (Sigma-Aldrich, H1270) in Dako buffer.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In this study, we confirmed the specificity of our antibody (EF14007; noncommercial antibody) for cleaved SNAP25 42 . Our antibody recognizes cleaved SNAP25 in human and rodent tissues injected with BoNT-A 42,60 . In the pig, cleaved SNAP25 was only detected in aboBoNT-A-injected animals and not in saline-injected controls, suggesting that the antibody detects specifically the cleaved SNAP25 also in pigs.…”
Section: Wound Inflammationmentioning
confidence: 99%